Analysis of ground potential distribution under lightning current condition - Gomes, Chandima; Sabry, Riyadh Z. (Universiti Putra Malaysia Press, 2017)
The grounding system of a lightning protection scheme is designed basically to avoid arcing and dangerous step potentials. The grounding impedance of the system varies depending on soil structure and frequency. This paper describes the effect of harmonic impedance (also called frequency dependence of soil) on potential distribution under lightning strike to a metal tower with single grounding path, for different soil types. The results show that the peak value of ground potential rise (GPR) and step voltage (SP) may reach extremely hazardous values even at distances in the order of 90 m from the tower footing, especially when soil resistivity is high. Hence, we emphasise that, in contrast to power grounding, when designing of grounding systems that are meant to handle transient or high frequency currents as well, the frequency dependent soil parameters should be considered to avoid hazardous situations, especially at locations with a high probability of lightning strikes such as metal towers.